2014
DOI: 10.4161/mabs.29111
|View full text |Cite
|
Sign up to set email alerts
|

Co-transplantation of human hematopoietic stem cells and human breast cancer cells in NSG mice

Abstract: Humanized tumor mice (HTM) were generated by the co-transplantation of human hematopoietic stem cells and human breast cancer cells overexpressing HER2 into neonatal NOD-scid IL2Rγ(null) (NSG) mice. These mice are characterized by the development of a human immune system in combination with human breast cancer growth. Due to concurrent transplantation into newborn mice, transfer of MHC-mismatched tumor cells resulted in solid coexistence and immune cell activation (CD4(+) T cells, natural killer cells, and mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 49 publications
1
27
0
1
Order By: Relevance
“…Previous studies in HSC‐transplanted NSG mice have reported primary tumor development, but with the exception of the study by Wang et al . (), the growth pattern was either not illustrated or largely heterogeneous (Rongvaux et al ., ; Schilbach et al ., ; Wege et al ., ). The apparent cancer tolerance in BRGS‐HIS mice was not only due to an overwhelming growth rate, since the slow‐growing MDA‐MB‐468 tumors were not rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in HSC‐transplanted NSG mice have reported primary tumor development, but with the exception of the study by Wang et al . (), the growth pattern was either not illustrated or largely heterogeneous (Rongvaux et al ., ; Schilbach et al ., ; Wege et al ., ). The apparent cancer tolerance in BRGS‐HIS mice was not only due to an overwhelming growth rate, since the slow‐growing MDA‐MB‐468 tumors were not rejected.…”
Section: Discussionmentioning
confidence: 99%
“…MHC-mismatched tumor cells resulted in activated immune cells, but no clinical signs of rejection were observedWege et al (2014)CervicalHuman cervical carcinoma cell line (C33a) was subcutaneously engrafted into scid miceHerpes simplex virus type I-based oncolytic treatment in combination with radiation therapy may be an effective treatment for cervical cancerBlank et al (2002)Colorectal Rag2 −/− γc −/− mice were injected with human PBMCs and subcutaneously engrafted on the flank with colorectal carcinoma cell line (HT-29)Co-administration of Urelumab and Nivolumab slowed down tumor growth by elevating activated human T lymphocytes which produced IFN-γ and decreased levels of human regulatory T cells in tumor xenograftsSanmamed et al (2015)GastricPatient-derived xenografts of gastric cancer were subcutaneously engrafted into the right hind flank of scid and nude miceMice engrafted with patient-derived gastric cancers demonstrated identical histological and genetic diversities which corresponded to parental patient tumorsZhang et al (2015)HNSCCNSG mice were injected with expanded HSPCs and engrafted with patient-derived HNSCCHuman immune and stromal cells produced in XactMice mimics patient’s tumor microenvironment. This model was able to reverse genetic drift of tumors that usually occur after serial transplantation in non-humanized miceMorton et al (2016)KidneyNSG mice were engrafted with human RCC cell line (SKRC-59 cells) in the left subrenal capsule of their kidneyHuman anti-CAIX mAbs inhibit RCC growth by halting migration and triggering immune-mediated killing of RCC.…”
Section: Models Of Human Diseases Established On Humanized Micementioning
confidence: 99%
“…One approach to achieve this is by incorporation of immune cells through co-transplantation of human CD34 + hematopoietic stem cells and breast cancer cells in immunodeficient mice (Wege et al, 2011, 2014). …”
Section: Building a Toolkit Fit For The Futurementioning
confidence: 99%